A STUDY OF ADVERTISING STRATEGIES IN HOTEL BROCHURES - Nuri, Istia Hamdiati (2013)
The present study entitled A study of Advertising Strategies in Hotel Brochures aims to find out the advertising strategies: concepting approaches (Altstiel & Grow, 2007) made by several hotels in their hotel brochures (Aston Tropicana, Amaris, Sensa, Nalendra and Favehotel) located on Cihampelas street Bandung. In addition, this study also evaluates those concepting approaches using AIDCA (Attention, Interest, Desire, Conviction, and Action) formula (Clyde Bedell, 1952; Albert & Schick, 1996; Bird, 2005, and Trehan, 2009). To analyze the data, a descriptive qualitative approach was applied. The findings show that four out of five hotel brochures consist of two concepting approaches namely show the benefit and show the product. In addition, it is found that there are three brochures used comparison as their approach. Overall, the evaluation result of those advertising strategies indicates that the AIDCA formula fail to be utilized by all of the hotel brochures on Cihampelas street Bandung since none of the hotel brochures applied AIDCA formula completely. Keyword: advertising, advertising strategies, hotel brochure, concepting approaches, AIDCA formula.